2015
DOI: 10.1186/s12876-015-0324-0
|View full text |Cite
|
Sign up to set email alerts
|

Intrahepatic cholestasis of pregnancy: observational study of the treatment with low-dose ursodeoxycholic acid

Abstract: BackgroundTo exam the biochemical, obstetric management and pregnancy outcome in women with intrahepatic cholestasis of pregnancy (ICP) and treatment with ursodeoxycholic acid (UDCA).MethodsPregnancy outcome in patients with ICP (N = 307) was studied and patients treated with UDCA (N = 208) vs. no UDCA were compared. The data of the antenatal visits, deliveries and neonatal outcome of 307 pregnancies with ICP was collected from the hospital computerized delivery room log book. UDCA was used in 208 pregnancies.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 29 publications
0
13
0
Order By: Relevance
“…However, co-treatment of TC with 1 μM of UDCA was effective in protecting against such CV slowing. Reflecting the clinical safety of UDCA in fetal and maternal hearts,[ 19 ] treatment of hearts with UDCA alone did not produce any adverse changes in this study. Furthermore, a significantly smaller decrease in CV (−7.4±1.8%; P <0.05) was observed in the maternal hearts compared to the decrease in the fetal hearts ( Fig 2A and 2B ).…”
Section: Resultsmentioning
confidence: 60%
“…However, co-treatment of TC with 1 μM of UDCA was effective in protecting against such CV slowing. Reflecting the clinical safety of UDCA in fetal and maternal hearts,[ 19 ] treatment of hearts with UDCA alone did not produce any adverse changes in this study. Furthermore, a significantly smaller decrease in CV (−7.4±1.8%; P <0.05) was observed in the maternal hearts compared to the decrease in the fetal hearts ( Fig 2A and 2B ).…”
Section: Resultsmentioning
confidence: 60%
“…Currently, UDCA is the most promising treatment for ICP [38].First Palma et al reported UDCA improved significantly serum biochemistry in patients with ICP at 1992 [39].Initial pilot studies in ICP followed by controlled trials demonstrated that UDCA improved pruritus and liver tests and had no maternal or neonatal adverse effects [39,40].Since that time, there have been several studies and additional case series demonstrating that UDCA treatment results in clinical and biochemical improvement in ICP [41,42].Studies examining the bile acid pool composition have shown that, in addition to a reduction in the serum bile acid concentration, treatment with UDCA results in a normalization of the CA:CDCA ratios, and a reduction in urinary excretion that is associated with reduction in pruritus [43].The mechanism underlying the beneficial effect of UDCA is unclear. UDCA has been shown to correct the impaired bile acid transfer kinetics observed in ICP placentas and to reverse the morphological changes seen in the placentas of a rodent model of ICP.…”
Section: Ursodeoxycholic Acidmentioning
confidence: 99%
“…Intrahepatic cholestasis of pregnancy (ICP) is a pregnancy-related liver disorder with a condition of severe pruritus combined with elevated liver function during the second or third trimester of pregnancy, and symptoms resolve spontaneously within 2-3 weeks after delivery (Joutsiniemi, Timonen, Linden, Suvitie, & Ekblad, 2015). The mother experiences intense, disturbing itching (Lammert, Marschall, Glantz, & Matern, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…UDCA appears to be the most efficient pharmacologic treatment. It has been shown that UDCA ameliorates pruritus and restores elevated liver function during ICP (Joutsiniemi et al, 2015;Joutsiniemi, Timonen, Leino, Palo, & Ekblad, 2014;Kondrackiene, Beuers, & Kupcinskas, 2005), without interfering with fetoplacental estrogen production (Joutsiniemi et al, 2014). It was more effective than cholestyramine and dexamethasone at reducing bile acid concentration (Kondrackiene et al, 2005).…”
Section: Introductionmentioning
confidence: 99%